2018
DOI: 10.1155/2018/7346835
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of 1,3,8-Triazaspiro[4.5]decane-2,4-dione Derivatives as Myelostimulators

Abstract: Spiroconnected N-alkoxyalkylpiperidine hydantoins were obtained via the Strecker reaction of cyanohydrin with ammonium carbonate. 1,3,8-Triazaspiro[4.5]decane-2,4-diones have shown the myelostimulating activity in the artificially induced (with cyclophosphamide) myelodepressive syndrome. The compounds significantly accelerated the regeneration of lymphocyte and granulocyte cell pool of bone marrow hematopoiesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This has prompted us to prepare a series of new structural analogs of these lead compounds and evaluate them pharmacologically to assess their antiviral and antitumor potential. The results are reported in this paper 5 .…”
Section: Introductionmentioning
confidence: 72%
“…This has prompted us to prepare a series of new structural analogs of these lead compounds and evaluate them pharmacologically to assess their antiviral and antitumor potential. The results are reported in this paper 5 .…”
Section: Introductionmentioning
confidence: 72%
“…Recently it was found that some of the compounds exhibiting mielostimulating activity [14,15] also show growth stimulating activity [16], moreover, most of these ionic compounds were found to be non-toxic towards A. Fischeri which make them promising sustainable and environmentally friendly growth stimulants. Herein we report about the synthesis and growth regulating activity of new ionic compound obtained via N-alkylation of trimecaine.…”
Section: Introductionmentioning
confidence: 99%